Progressive Muscle Relaxation to Reduce Pain - Prihanto Prihanto; Caecilia Titin Retnani (Jurnal Ilmiah Permas: Jurnal Ilmiah STIKES Kendal, 2020)
Comfort is a basic human need, one of problem from comfort is pain. Acute pain occurs less than three month and chronic pain that occurs more than three months. One of the pain management used by nurses is non pharmacological methods, namely is progressive muscle relaxation techniques. Objectives provide overview of the application of progressive muscle relaxation. The study used the literature review method, the search for articles from the Sciencedirct, Proquest, Researchgate, Google data base, from 2010 until 2020. Progressive muscle relaxation techniques as a technique to reduce pain as an alternative or complementary technique. This technique is used on client with acute pain and chronic pain clients such as cancer. Techniques need guidance by experts one of which is a nurse. Duration of about 10-20 minutes, the principle of providing peace of mind. Progessive Muscle Relaxation techniques can reduce pain, so that can be used by nurses in the management of client with pain.